Green - Seeger, Laura Vaccaro (New York : Roaring Brook Press, 2012)
Illustrations and simple, rhyming text explore the many shades of the color green.
On die-cut pages.
"A Neal Porter book"--T.p.
Wilson's Children, October 2012
School Library Journal starred, March 2012
Booklist starred, May 2012
Horn Book Starred, March 2012
Keywords: Green -- Juvenile fiction; Toy and movable books -- Specimens; Green -- Fiction; Stories in rhyme; Toy and movable books; Green -- Fiction; Stories in rhyme; Toy and movable books